Incidence and outcomes of endophthalmitis with in-house compounded intravitreal bevacizumab injections: A multicentric study. (18th August 2021) - Sen, Sagnik; Mishra, Chitaranjan; Kannan, Naresh Babu; Ramasamy, Kim; Rameshkumar, Gunasekaran; Lalitha, Prajna
ABSTRACT: Purpose: To evaluate the incidence rate and outcomes of endophthalmitis after intravitreal injection of in-house compounded bevacizumab. Methods: In this multicentric study performed from 2014 to 2018, patients who were injected with in-house compounded and sterilized bevacizumab were observed for endophthalmitis. In-house compounded syringes were prepared in compounding pharmacy using sterile standard operating guidelines. All cases of acute endophthalmitis following intravitreal injection were recorded and followed up for final anatomical and visual outcome after management. Results: A total of 50, 361 bevacizumab injections were administered. Incidence of post-injection endophthalmitis was 0.0377%. Incidence of culture-positive endophthalmitis was 0.0178%, with 55.5% culture positivity for Staphylococcus species. A significant improvement in the final visual outcome was noted ( p <0.05), and overall five patients (26.3%) achieved visual acuity of 6/18 or more. Conclusions: In-house compounded injections of bevacizumab can reduce post-injection endophthalmitis to a minimum, with maintenance of proper asepsis and strict protocols by the compounding pharmacy.